Hidrólise enzimática da proteína do farelo de soja - Ströher, Raquel (2010)
Great interest is shown by soy bran, by its availability as a by-product of oil extraction industry. It has a variety of applications, such as the enrichment of foodstuffs and protein isolates and concentrates, although most soy bran is still intended to feed. Many processes have been developed with the goal of getting more refined products intended for human consumption or directly to the production of ingredients with proteins (additives). This study was performed at the solubilising of soy bran protein by enzymatic hydrolysis to later, to study the feasibility of incorporating the hydrolyzate in fruit nectar. The enzyme was held in solubilising pH of 6,5, near suspension under temperature of 60 °C and agitation 100 rpm in hatchery. The enzyme Alcalase was added to a concentration of 1% protein/protein. After 3 hours of catalytic activity, the reaction was completed by ice bath immersion. The total amount of protein solunilized by the enzyme was 28,16 mg/mL, ie, considering that soybean meal has 47% protein, the enzyme Alcalase solubilized 60% of the protein initially present. The degree if hydrolysis (DH) obtained was 28%. A high value was expected, since the enzyme was able to solubilize the protein to form peptides smaller, more soluble, then the amount of peptides bonds broken was large, resulting in a high value of DH. In relation to the control of microbiological analysis and own protein hydrolyzates, analyzed samples parameters were within the range prescribed by existing laws for these types of product. The sensory analysis showed that for all the flavors, the product with 25% had greater acceptance of the products with 50 and 80% dissolved in nectar. And even products with 50% soluble in nectar obtained greater acceptance of the products with 80% concentration. Yet we saw that, for the same concentration of hydrolyzate, there was no significant difference between the acceptance flavors. A fact observed the same in products with low hydrolyzate protein concentration was the strong taste bitter, resulting from the release of hydrophobic groups. It is evident the need for some procedure that remove or masks the bitter taste of hydrolyzed proteins, for example, treatment with activated charcoal, employment of cyclodextrins and use of liquid chromatography.